Knowledge Management Implementation to Improve Performance in Testing and Subsea Division at Big Red Company - Rahmadita, Amadea (Journal of Economics and Business UBS, 2023)
The approaching retirement of experienced petroleum engineers and technical staff, which threatens to result in the loss of a significant quantity of cumulative knowledge and expertise, is one of the major challenges facing the industry. Within the next ten years, it is predicted that approximately 231,000 years of collective knowledge will be on the line. To overcome this difficulty, knowledge management has emerged as a major method. This research investigates the strategies, tools, and processes implemented to successfully capture, organize, and share knowledge across the organization through a thorough analysis of the KM initiatives undertaken by Big Red Company. With a focus on their effective application by national and international oil companies in Indonesia, it also examines the results and impacts of these KM practices on the company's performance and competitiveness in both local and global contexts. Considering these circumstances, the company needs to improve the knowledge management system for managing knowledge, which is through the implementation of a Knowledge Management (KM) system. In doing this, the research is based on two research questions. The first is how is the current Knowledge Management maturity level in the Big Red Company Operation Division, specifically in the Testing and Subsea, and the second is What is the knowledge management implementation plan that can be suggested related to the proposed knowledge management process after knowing the maturity level of knowledge management in Big Red Company. These two research questions will be answered using theories related to knowledge, knowledge management, and two knowledge management frameworks, namely APO Knowledge Management Framework and Socialization, Externalization, Combination, Internalization (SECI). Because a qualitative method is used in this research, data is collected through interviews and observations, which are then analysed using thematic analysis. The results of data collection show that there are several issues related to the APO KM Framework and SECI frameworks. These issues range from the limited in the Testing and Subsea division, which is in Operation Division, the lack of knowledge sharing processes within and between teams, the lack of proper knowledge transfer, difficulty in accessing knowledge and information due to manual access, and others. Through the utilization of APO KM Framework and SECI frameworks, the author was able to design a knowledge management system by formulating several tools, for example, Coaching, Training, Knowledge café, Lesson-learned documents, K-based exit interview, and e-learning. With a total of 12 (thirteen) knowledge management tools or techniques, the company now has the ability to identify the knowledge needed, capture the knowledge, store the knowledge, share the knowledge, and effectively utilize knowledge and information which can improve the organization’s performance, enhance decision-making processes, and foster innovation and collaboration, thereby gaining a competitive advantage in the lifting equipment industry which ultimately contributes greatly to the growth of the company. For the knowledge management system implementation process, it will be divided into 5 (five) stages: Preparation, Identification, Development, Implementation and Evaluation to ensure that the knowledge management system is implemented effectively, its impact can be measured, and areas for improvement can be identified to make necessary changes. Implementation will begin in January of 2024, and there will be a dedicated Person In Charge (PIC) for all knowledge management initiatives to monitor the progress and ensure the sustainability of this system.